Implementation of sedimentary facies and diagenesis on the reservoir quality of the Aquitanian‐Burdigalian Rudeis Formation in the Gulf of Suez, Egypt: A comparative surface and subsurface study. (29th November 2019) - Nabawy, Bassem S.; Mansour, Ahmed S.; Rashed, Mohamed A.; Afify, Walaa S.M.
Abstract : The Lower Miocene Rudeis Formation has been studied in two surface outcrops on the eastern onshore of the Gulf of Suez at Wadi Wasit and Sarbut El Gamal localities and in the subsurface sequence of October oil field in the central part of the Gulf of Suez. A correlative study between the subsurface sequence and its surface analogs was carried out to assess the reservoir quality of the Rudeis Formation and the impacts of the lithofacies, microfacies, pore types and dominant diagenetic processes on its reservoir quality. The Rudeis Formation consists of a thick carbonate‐clastics succession. The lower part consists of a cyclic sequence of laminated, fossiliferous and argillaceous limestone intercalated with mudstone, and sandstones. These units are unconformably overlain by alternations of conglomerate, coarse sandstones, and limestones. It is documented that the clastic microfacies have good reservoir quality in the October Field and poor quality in Wadi Wasit. This is due to the impacts of dissolution and fracturing diagenetic processes. The carbonate microfacies are impervious due to effects of cementation, mechanical compaction, quartz overgrowth, authigenic minerals, and micritization.